Gaze instability after exposure to moving visual stimuli in patients with persistent postural-perceptual dizziness - Yagi, Chihiro; Morita, Yuka; Yamagishi, Tatsuya; Ohshima, Shinsuke; Izumi, Shuji; Takahashi, Kuniyuki; Itoh, Kosuke; Suzuki, Yuji; Igarashi, Hironaka; Horii, Arata (Frontiers in Human Neuroscience, 2022)
Persistent postural-perceptual dizziness (PPPD) is a chronic vestibular syndrome lasting more than 3 months. The core vestibular symptoms are dizziness, unsteadiness, and non-spinning vertigo, which are exacerbated by upright posture or walking, active or passive motion, and exposure to moving or complex visual stimuli. Among these, visual exacerbation is a key feature of PPPD for which the neural mechanisms are unknown. We hypothesized that vestibular symptoms may be exacerbated by visual stimuli through gaze behavioral change after exposure to moving or complex visual stimuli. The study aimed to examine gaze stability after exposure to moving visual stimuli in patients with PPPD. Fourteen healthy controls (HCs), 27 patients with PPPD, and 12 patients with unilateral vestibular hypofunction (UVH), showing chronic vestibular symptoms for >3 months, were enrolled in the study. The participants were instructed to fixate on the gazing point at the center of a screen for 30 s before and after 90 s of exposure to moving visual stimuli. Gaze stability, best represented by the bivariate contour ellipse area (BCEA), was compared among three groups, both before and after exposure to the moving visual stimuli. Comparisons between pre- and post-moving visual stimuli in BCEA were also conducted. Correlation between the post/pre ratio of BCEA and vestibular tests, several clinical symptom scales including the Dizziness Handicap Inventory, Niigata PPPD Questionnaire, and Hospital Anxiety and Depression Scale, and the exacerbation of dizziness by exposure to moving visual stimuli was examined in the PPPD group. BCEA, both before and after exposure to moving visual stimuli in the PPPD group, was not different from that in HC and UVH groups. In the PPPD group, BCEA increased significantly after exposure to moving visual stimuli. The post/pre ratio of BCEA correlated with the occurrence of exacerbation of the dizziness sensation by exposure to moving visual stimuli; however, it did not correlate with vestibular tests or clinical symptom scales. Patients with PPPD were more likely to exhibit gaze instability after exposure to moving visual stimuli, which potentially exacerbated vestibular symptoms. This phenomenon may help elucidate the neural mechanisms of visual exacerbation in patients with PPPD.